(untitled) (JBN (Jurnal Bedah Nasional), 2026)
One of the congenital abnormalities that can be found in children is congenital diaphragmatic hernia. The prevalence of left-sided congenital diaphragmatic hernias is higher than right-sided congenital diaphragmatic hernias. This situation causes organs in the abdominal cavity to be pushed into the thoracic cavity. The diagnosis of this condition can usually be made when the patient is still a baby, both clinically and radiologically. The appropriate treatment that can be done for patients with this condition is surgery. In this case report, we describe a patient with a right congenital hernia which was confirmed based on clinical findings and radiology results. The patient underwent surgery in the form of a hernia repair. This case report also discusses the management of a patient with a right congenital hernia.